Efficacy of School-health Modifier Management Package in Managing Delinquent Behaviours of Adolescents in Secondary Schools in Ikpoba-Okha LGA, Edo State, Nigeria - Obasuyi, Osato Harriet; Oronsaye, Osaiyekemwen Douglas; Obasuyi, Efosa Samuel (NIU Journal of Educational Research; Vol 11 No 2 (2025): NIU Journal of Educational Research, Vol. 11, No. 2, June 2025DO - 10.58709/niujed.v11i2.2213, 2025)
The paper assessed the efficacy of School-health Modifier Management Package to manage delinquent behaviours of adolescent in secondary schools in Ikpoba-Okha LGA. Four research questions, out of which three were hypothesized and tested at 0.05 level of significance were addressed in the study. A quasi-experimental research design in the form of a pre-test post-test non-equivalent control group design was used for the study. Six thousand and seventy-five (6075) public senior school students in ten schools in the LGA was used. 192 adolescents were randomly selected with multistage sampling procedure and were divided into two groups in accordance with their exposure to the Adolescent Delinquent Questionnaire and one group to the School-Health Modifier Management Package. The package was validated and its reliability was 0.77. In addition, the questionnaire was validated and its reliability established at 0.78. Data obtained were analysed with on-way analysis of covariance. Findings showed that majority (50.0%) of adolescents in secondary schools in Ikpoba-Okha LGA have moderate level of delinquent behaviour while 30.7% and 19.3% were mild and severe respectively. Findings also indicated statistically significant difference in post-intervention management of mild, moderate and severe delinquent behaviours of adolescents with SMMP, between the experimental and control groups when adjusted for pre-intervention. It was recommended that health educators and stakes at the Ministries of Education and Health should collaborate with the researchers to use the School-Health Modifier Management Package in Oredo, or other Local Government Areas and the entire State to address the social menace of delinquency in secondary schools.  Keywords: School-health, modifier, management, package, adolescent, delinquent behaviour, delinquency.